Concentration, spatial distribution, and health risk assessment of PFASs in serum of teenagers, tap water and soil near a Chinese fluorochemical industrial plant - Lin-Na Xie (Environment International, 2021)
Discharges released from fluorochemical industrial plants lead to severe contamination of the environment with per- and polyfluoroalkyl substances (PFASs), which may pose risks to human health. In this study, 187 serum samples from teenagers (age = 14 years), 22 tap water samples and 40 soil samples were collected in areas within 0–11 km of a fluorochemical industrial plant in Huantai County, Shandong Province, and concentrations of 18 PFASs were quantified by UPLC-MS/MS. Perfluorooctanoic acid (PFOA) was found to be predominant, concentrations of which ranged from 40.4 to 845 ng/mL in serum, from 2.88 to 19.3 ng/L in tap water, from 4.40 to 189 ng/g in soil, and accounting for 84.1–98.6%, 15.9–79.8%, and 73.8–96.7% of the total PFASs, respectively. Statistical analysis demonstrated that concentrations of perfluorinated carboxylic acids (PFCAs) in soil (C5-C9) and serum (C8-C10) were associated with the industrial plant. And PFOA concentrations in tap water were not relevant to the industrial plant, which were comparable with the non-contaminated area and lower than the threshold value recommended by U.S. EPA (70 ng/mL), indicating that the contribution to the high concentration of serum PFOA of local teenagers by drinking water was limited. Moreover, PFCAs in soil only made a limited contribution to the serum PFCAs of local residents by direct inhalation and dermal exposure, but the potential health risk by the soil via food chain should be paid attention to. Furthermore, health risk assessment demonstrated that high concentrations of PFOA in serum could pose potential health risk to local teenagers. Therefore, effective measures should be taken to attenuate the health risks caused by the industrial plant to local residents, and further epidemiological studies should be carried out in the future.